Movement profiles of elite women soccer players during international matches and the effect of opposition`s team ranking - Hewitt, A.; Norton, K.; Lyons, K. (Journal of Sports Sciences, 2014)
Movement patterns in elite men`s soccer have been reported in depth, but less research exists for women`s soccer. Aims of the study were to identify the movement profiles of elite women soccer players in international competition and examine the effect the level of opposition, based on Federation Internationale de Football Association (FIFA) rankings, had on the physical demands of the game. MinimaxX athlete tracking devices were used by 15 players during 13 international matches against opponent teams of varying ability. Total distance covered averaged 9292 ± 175 m. There was a decrease in high-intensity running (HIR) in the 60- to 75-min and 75- to 90-min periods compared to the 0- to 15-min period of 22.4% and 26.1%, respectively (P = 0.022, P = 0.004) although sprint distances remained unchanged across game periods. HIR distances covered were significantly greater for midfielders versus defenders, while defenders had lower sprinting compared to both midfielders and attackers. Stronger opponents elicited less HIR and greater low-speed activity (LSA) compared to playing teams of similar or lower ranking. These results are important to coaches to prepare players for international competition and show the differing demands required depending on the ability of the opponents.